Anesthetic Management of a Surgical Patient with Chronic Renal Tubular Acidosis Complicated by Subclinical Hypothyroidism - Hiroe Yoshioka; Haruyuki Yamazaki; Rie Yasumura; Kosuke Wada; Yoshiro Kobayashi (Case Reports in Anesthesiology)
A 53-year-old man with chronic renal tubular acidosis and subclinical hypothyroidism underwent lower leg amputation surgery under general anesthesia. Perioperative acid-base management in such patients poses many difficulties because both pathophysiologies have the potential to complicate the interpretation of capnometry and arterial blood gas analysis data; inappropriate correction of chronic metabolic acidosis may lead to postoperative respiratory deterioration. We discuss the management of perioperative acidosis in order to achieve successful weaning from mechanical ventilation and promise a complete recovery from anesthesia.